A strong argument for using non-commodities to generate electricity - Tatiana Marques Santiago, Katarina (2009)
An optimal control approach towards generating electricity is used to analyze the trade-off between the use of primary sources which are regarded as commodities, such as fossil fuels, biomass and water, and their other economic uses (for example, in the petrochemical industry, in the production of fuels, in agriculture, in steelmaking, and so forth). In order to do so, a dynamic model is presented which establishes relationships between economic growth, the fossil fuel, water and biomass sectors, and energy policies, based on the application of the Pontryagin Maximum Principle. Among other results, the analysis establishes that, in the optimal path, the price of commodities for non-energy uses should be twice the price of the energy assets, which indicates the need to use sources which are not commodities such as solar energy, wind energy, and geothermal energy, to generate electricity